Dendrimers as Powerful Building Blocks in Central Nervous System Disease: Headed for Successful Nanomedicine - Leiro, V (2017)
Dendrimers have emerged as a powerful class of nanomaterials in the nanomedicine field due to their unique structural features: globular, well-defined, highly branched and controllable structure, nanosize-scale, low polydispersity, and the presence of several terminal groups that can be functionalized with different ligands simulating the multivalency present in different biological systems. Although in its infancy, the application of dendrimers as therapeutics or theranostic tools in central nervous system (CNS) disorders is already significant and has opened promising avenues in the treatment of many conditions where the inherent "smartness" of the dendritic structures is being explored to effectively target the CNS. Here we present an overview of the past and future challenges of the use of dendrimers to respond to one of the ultimate challenges in the (nano)medicine field: to attain CNS repair and regeneration.